Rock Opera Seorang Seniman - Joyce Teo (Wacana Seni Journal of Arts Discourse, 2005)
The Malay rock music scene in Singapore was in its peak around the l 970s and l 980s. It was a golden era where many of the legendary bands were formed, talents came into the spotlight, concerts played to large crowds. And while bands from the west such as Black Sabbath and Led Zeppelin inspired many Malay rockers, what was unique about the Malay rock scene then, was that the rockers did not just do covers. They also wrote original songs with memorable melodies and heartfelt lyrics that expressed their aspirations and ideas about life.